Community Gerontology: A Framework for Research, Policy, and Practice on Communities and Aging. (13th August 2018) - Greenfield, Emily A; Black, Kathy; Buffel, Tine; Yeh, Jarmin
Abstract: We introduce "community gerontology" as an area of research, policy, and practice that aims to advance understanding of communities as fundamental contexts for aging and its diversity, and to leverage this understanding for change. We present a foundational framework for community gerontology in three parts. First, we discuss the mesolevel as the unifying construct for community gerontology. Second, we describe community gerontology's focus on pathways of mutual influence between the mesolevel with more micro and macro contexts over time. Third, we put forth community gerontology's emphasis on gerontologists' participation in community change processes to facilitate more optimal experiences of aging among diverse population subgroups. We conclude by describing the integrative nature of community gerontology and the ways that this framework can advance research on particular substantive areas, as well as gerontology as a whole.